2015
DOI: 10.1021/acs.jafc.5b00961
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Microwave Heating on Phytosterol Oxidation

Abstract: The oxidative stability of phytosterols during microwave heating was evaluated. Two different model systems (a solid film made with a phytosterol mixture (PSF) and a liquid mixture of phytosterols and triolein (1:100, PS + TAG (triacylglycerol))) were heated for 1.5, 3, 6, 12, 20, and 30 min at 1000 W. PS degraded faster when they were microwaved alone than in the presence of TAG, following a first-order kinetic model. Up to 6 min, no phytosterol oxidation products (POPs) were generated in both systems. At 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 45 publications
2
15
0
Order By: Relevance
“…Oxidative changes caused by MW heating not only affect the triacylglycerols in the lipid fraction of foods. Other components, such as sterols, may also be affected as reported by Leal‐Castañeda et al , who observed an important decrease in the content of different phytosterols and the consequent increase of their oxidation products (POPs) during MW heating of different mixtures of triolein‐phytosterols.…”
Section: Introductionmentioning
confidence: 81%
“…Oxidative changes caused by MW heating not only affect the triacylglycerols in the lipid fraction of foods. Other components, such as sterols, may also be affected as reported by Leal‐Castañeda et al , who observed an important decrease in the content of different phytosterols and the consequent increase of their oxidation products (POPs) during MW heating of different mixtures of triolein‐phytosterols.…”
Section: Introductionmentioning
confidence: 81%
“…Despite the fact that this method showed good recovery (98.7%) and repeatability (3.5 %, interday RSD), it used a common domestic microwave oven programmed at high potency (~350 W) without temperature control and these authors did not assay COPs nor evaluated artifact formation during saponification. On the other hand, Leal-Castañeda et al [11] showed that high power microwaves (1000 W, in a domestic multimodal equipment) can lead to phytosterol oxidation when heating time is higher than 6 min. Moreover, the use of domestic microwave oven is not recommended for analytical procedures using solvents because it does not have anti-explosion vessel safety features.…”
Section: Introductionmentioning
confidence: 99%
“…As suggested by Kraljić et al () thermally‐induced disruption of rapeseeds internal structure leads to oil release from cells which comes into contact with phytosterols during microwaving and increases their extractability into the oil. Leal‐Castañeda et al () investigated the oxidative stability of phytosterols in two different model systems (phytosterol film and a mixture of phytosterols and triolein), MV heated from 1.5 to 30 min at 1,000 W. The authors found that no degradation change of phytosterols was noticed between 3 and 12 min of microwaving; moreover, phytosterol oxidation products formation, in both model systems, was observed after 12 min of MV heating.…”
Section: Resultsmentioning
confidence: 99%